Determinants of non-reporting of social and environmental information by Malaysian companies - Noriah Che-Adam,; Phua , Lian Kee; Fauziah Md Taib, (Penerbit Universiti Kebangsaan Malaysia, 2012)

(untitled)
In Malaysia, most public companies do not provide social and environmental information in their annual reports. Given the importance of corporate social responsibility (CSR) to the sustainability of resources for future generations, this study attempts to identib; the determinants of non-reporting of social and environmental information from the perspectives of proprietary costs and information costs saving. This study analyses the content of annual reports of 368 Malaysian public listed companies. The results show that proprietary cost perspective can explain the non-reporting of social and environmental information while information costs saving perspective can only partially explain the decision. It is also noted that the absence of these drivers are caused by low ethical consumerism and lack of proactive measures by the various watch dog groups in Malaysia.